Toward a more coherent and profession-related physics teacher education: Linking subject-specific and physics education content in the study entry phase - Bauer, Antonia; Gleichmann, Jonas; Bitzenbauer, Philipp (American Journal of Physics, 2025)
The introductory phase of the physics teacher education program at the Friedrich–Alexander University Erlangen–Nuremberg (FAU), Germany, was redesigned to improve the coherence of the program and reduce the high dropout rates in the introductory phase of the physics teacher education program by making the courses more relevant and appealing to the students' future professional roles. The new organization combines subject-specific lectures on experimental physics with a simultaneous presentation of the corresponding perspectives of physics education through a new course called “Focus Class: physics education and school-related topics.” This new course is directly linked to the subject-specific content of the lecture and focuses on the conceptual hurdles that school students may encounter when confronted with the subject matter being taught in lectures and emphasizes active learning strategies. In this paper, we describe the course design and report on student experiences from an evaluation of the cours
Keywords: Curriculum development; Physics education research; Teacher training